Settlement of Inheritance Disputes in the Perpsketif of Religious Court Decision Number 400/Pdt.G/2022/Pa.Sel - Zulkarnain; Aaz Jidatul Haz; Muhammad Maghfurrohman; Nur Hastuti Bima Putri; Khairul Hamim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
. In handling dispute resolution through litigation, judges are required to provide decisions that are as fair as possible for the parties involved in the dispute. He must consider all aspects related to the subject of the dispute so that his decision is truly considered to provide justice. So one of the disciplines that is very important for a judge to help him in making decisions is qawaid al fiqhiyah. In the context of legal determination, fiqh rules play an important role as 'analytical knives' considering the legal problems they face. In case decision Number 400/Pdt.G/2022/PA.Sel, the Selong Religious Court, East Lombok Regency, has won for the defendants regarding the proposed inheritance dispute. In this decision, the judge used two qawaid fiqh as legitimacy for his legal considerations. This research aims to analyze the judge's considerations using fiqh rules and their relevance to the inheritance dispute cases they handle. This research is descriptive-analytic in nature, namely carrying out data analysis by enriching information, looking for relationships, comparing, finding patterns on the basis of original data. then analyze it using the Content Analysis method. The primary data source is decision text Number 400/Pdt.G/2022/PA.Sel, while secondary data was obtained through literature study. The research results show two conclusions. Firstly, the judge uses fiqh rules as a basis for consideration in determining the subject of the dispute, namely whether the heir's assets have been divided or not. Second, the judge's decision was handed down using a scientific approach.